Resolution of the systematic status of Eublepharis macularius fuscus Boerner, 1981 (Eublepharidae: Sauria: Squamata) - Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 1997)
The disjunct population of leopard geckos, genus Eublepharis from western India (Gujarat, Maharashtra and Karnataka) is shown to be non conspecific with E. macularius. Originally described as a subspecies of E. macularius by Borner (1981), E. fuscus is demonstrated to be both diagnosable and allopatric with congeners, and therefore elevated to species status and a neotype designated. Eublepharis fuscus differs from known congeners in possessing the following combination of characters: six postnasals contacting nasals; eight supralabials to a point below pupil; mental small, hexagonal, longer than wide and about twice as long as the first pair of postmentals; prefrontal region with smooth, flat scales,; large granular and non-spinose tubercles on the dorsum.